1993
DOI: 10.1016/0014-5793(93)81397-i
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional expression of a brain G‐protein‐coupled ATP receptor

Abstract: A cDNA encoding a novel member of the G-protein-coupled receptor (GCR) superfamily. an ATP receptor, has been isolated from an embryonic chtck whole brain cDNA hbrary by hybridizatton screenmg. The encoded protein has a sequence of 362 amino acids (41 kDa) and shares no more than 27% amino acid identity with any known GCR. When expressed as a complementary RNA (cRNA) m Xenopus oocytes a slowly-developing inward current was observed in response to application of ATP. The pharmacology of this expressed protem de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
340
2
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 513 publications
(355 citation statements)
references
References 28 publications
11
340
2
2
Order By: Relevance
“…In 1993, the first receptors for nucleotides, called P2 purinoceptors, were cloned46, 47. Afterwards, numerous subtypes of these receptors were also cloned, and subsequently scientists began to gradually accept the ‘purinergic system.’ Now purinergic P2 receptors are divided into two families, ionotropic receptors (P2X) and metabotropic receptors (P2Y).…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 99%
“…In 1993, the first receptors for nucleotides, called P2 purinoceptors, were cloned46, 47. Afterwards, numerous subtypes of these receptors were also cloned, and subsequently scientists began to gradually accept the ‘purinergic system.’ Now purinergic P2 receptors are divided into two families, ionotropic receptors (P2X) and metabotropic receptors (P2Y).…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 99%
“…This classification has recently been expanded (Abbracchio and Burnstock, 1994;Barnard et al, 1994) to accommodate the results of cloning studies that revealed the existence of multiple subclasses of P2y purinoceptors Webb et al, 1993;Parr et al, 1994). Activation of the two major subclasses of G-proteincoupled receptors, P2Y(P2Y1) and P2U(P2Y2)' results in phospholipase C-catalysed hydrolysis of phosphatidylinositol 4,5-bisphosphate and consequent inositol 1,4,5-trisphosphate-mediated release of calcium from intracellular stores (Boarder et al, 1995).…”
mentioning
confidence: 99%
“…In freshly dissociated limb cells, large increases in [Ca 2ϩ ] i were elicited by ATP, ADP, and 2MeSATP (a synthetic analogue of ATP that is a potent agonist of the recombinant cP2Y 1 receptor expressed in Xenopus oocytes, Webb et al, 1993;Simon et al, 1995) at concentrations of 100 M and 10 M. Figure 2 shows typical [Ca 2ϩ ] i increases in single cells or small clusters of cells to these nucleotides. A small Ca 2ϩi transient was also detected in response to 100 M UTP (Fig.…”
Section: Monitoring Intracellular Free Calcium Levels Demonstrates Thmentioning
confidence: 99%
“…P2X receptors are members of the ligand-gated ion channel superfamily, whereas P2Y receptors constitute a family of G protein-coupled receptors for extracellular nucleotides. Activation of the P2Y receptor cP2Y 1 by extracellular ATP leads to mobilization of intracellular calcium (Ca 2ϩi ) and activation of protein kinase C (PKC) (Webb et al, 1993;Simon et al, 1995). Mobilization of Ca 2ϩi , and the cascade of intracellular protein phosphorylation initiated by activation of PKC, are important regulators of cell growth and differentiation (Berridge, 1993;Lauder, 1993), and there is now considerable evidence supporting a role for P2Y receptor signaling in regulating long-term changes in cell proliferation and differentiation (reviewed in Abbracchio, 1996;Neary and Burnstock, 1996).…”
Section: Introductionmentioning
confidence: 99%